ANALYSIS AND STRUCTURING THE COMPOSITION OF THE GARDEN OF EDUCATION FIELD OF SANTA MARIA (CISM) FOR LOCAL COMMUNITY - Gracioli, Cibele Rosa; Bohner, Tanny Oliveira Lima; Redin, Cristina Gouvêa; Silva, Daniela Thomas da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The Education Field of Santa Maria (CISM) is a private Army area, located in the district of SaintValentine and currently used for conducting military maneuvers and eventually serving as a placeto community visitation. At this place, there are fragments of native vegetation, as well asspecimens of this flowering composes the CISM surrounding landscape. This flora is preserved inpart due to lack of users awareness. This study aims to propose a planning and landscaping designwithin the precepts of environmental education techniques. According to the observations and evaluations, it was observed that the tropical garden composition is the most appropriated, sincethe most present species are used in these compositions. In this sense, the place was visited andthe photographic recording of the species, such as its correct identification and variables ofdendrometric interest surveys, were accomplished. Through environmental education techniques,it is possible to suggest a landscaping composition suitable for the existing species andarchitectural elements